Strategic Integration of Islamic Boarding School Curriculum and Digital Learning for Enhacing The Quality of Islamic Education - Muhammad Zainulloh; Agus Timan; Raden Bambang Sumarsono; Qisthi Efridita (Universitas Nurul Jadid, 2026)
This study aims to map strategies for integrating Islamic boarding school (pesantren) curricula with the implementation of digital learning in enhancing the quality of Islamic education in the Society 5.0 era. Employing a Systematic Literature Review (SLR) method guided by the PRISMA framework, this study analyzes 27 scholarly articles indexed in SINTA and Scopus published between 2020 and 2026. The findings of the literature synthesis reveal that the integration strategy is implemented through a subject-based curriculum model that aligns kitab kuning (classical Islamic texts) with digital competency standards without compromising the distinctive identity of pesantren. The digital ecosystem is developed through the adoption of smart classrooms, digital edutainment, and adaptive instructional leadership. Despite challenges such as infrastructure disparities and cultural resistance, managerial solutions through the boarding school model and digitally based academic supervision have proven effective in mitigating these risks. This study concludes that the transformation of the quality of Islamic education depends on the institutional capacity to balance spiritual traditions with globally competitive 21st-century skills.